GAMBARAN TINGKAT KOGNITIF PADA LANSIA DI DESA LEBIH BANJAR DUUR KAJA GIANYAR - Ni Made Melati Dewi; Putu Intan Daryaswanti (Bali Health Published Journal, 2020)
Background: Cognitive level is a mental process or physical or thought activity that leads to the role of perception, ability, memory and thought processes possessed by every human being. The incidence of cognitive decline in Indonesia in 2019 as many as 47% of elderly experience a decrease in cognitive level. The occurrence of changes and setbacks in the cognitive level in the future will have an impact on the health of the elderly one of which is, a decrease in memory and changes in memory. This study aims to determine the cognitive level in the elderly in the village of more Banjar Duur Kaja Gianyar in 2020. Method: This study used a descriptive research method with cross sectional approach, the measuring instrument used in this study was the MMSE (Mini Mental State Examination) questionnaire. The population in this study is the elderly who live in the village of more Banjar Duur Kaja Gianyar with a total sample of 47 samples. The sampling technique used in this study was purposive sampling. Results: The results of the study of 47 elderly, the cognitive level of the elderly in the category of probable cognitive levels. Respondents with age > 60 are 18 elderly (45%) have a probable cognitive level. Respondents who were not educated 15 elderly (36.59%) had a probable cognitive level. Respondents who did not work 8 elderly (38.10%) had a probable cognitive level. 11 male respondents (44%) had a probable cognitive level. Conclusion: The cognitive level of the elderly in the village of more Banjar Duur Kaja Gianyar is in the category of probable cognitive level of 19 elderly (40.4%).